EGCG Nanoparticles Attenuate Aluminum Chloride Induced Neurobehavioral Deficits, Beta Amyloid and Tau Pathology in a Rat Model of Alzheimer’s Disease - Singh, Neha Atulkumar; Bhardwaj, Vaishali; Ravi, Chandrika; Ramesh, Nithya; Mandal, Abul Kalam Azad; Khan, Zaved Ahmed (Frontiers in Aging Neuroscience, 2018)
Rational: Alzheimer’s disease is a neurodegenerative pathology characterized by the presence of senile plaques and neurofibrillary tangles. Aluminium has been reported to play an important role in the aetiology and pathogenesis of this disease. Hence, the present study aimed to evaluate the neuroprotective role of epigallocatechin-gallate (EGCG) loaded nanoparticles (nanoEGCG) against aluminium chloride (AlCl3) induced neurobehavioral and pathological changes in Alzheimeric rats. Method: 100 mg/kg body weight AlCl3 was administered orally for 60 days, which was followed by 10 mg/kg body weight free EGCG and nanoEGCG treatment for 30 days. Morris water maze, open field and novel object recognition tests were employed for neurobehavioral assessment of the rats. This was followed by histopathological assessment of the cortex and the hippocampus in the rat brain. Further validation was done, with biochemical, immunohistochemistry and western blot assays. Result: Aluminium exposure reduced the exploratory and locomotor activities in open field and significantly reduced the memory and learning curve of rats in Morris water maze and novel object recognition tests. These neurobehavioral impairments were significantly attenuated in nanoEGCG treated rats. Histopathological assessment of the cortex and hippocampus of aluminium-exposed rat brains showed the presence of both senile plaques and neurofibrillary tangles. In nanoEGCG treated rats this pathology was absent. Significant increase in biochemical, immunohistochemical and protein expression levels was noted in aluminium-exposed rats, while these levels were greatly reduced in nanoEGCG treated rats. Conclusion: In conclusion, this study strengthens the hypothesis that EGCG nanoparticles can reverse memory loss, senile plaque and neurofibrillary tangles formation.